The Effect of Integration by Bio-fertilization, Organic and Metallic in the Growth of the Product and the Output of Luz-be-otono and Absorption of Some Nutrients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
An  experiment was conducted by using pots contain 15 kg  of slity sand soil collected from one located in Al-diwania river, Al-Qadisiya province to studythe effect of integrated fertilizers bio,organic and mineralfertilizer in growth and yield of broad bean cultivar Spain (varietyLuz -be -otono)in growth season of 2015-2016. The experiment included inoculation of probiotic(bio health),application oforganic fertilizer,(50&100)% mineral fertilizer and their interaction as well as by using complete randomized design(CRD).After full pods filling , the growth features, height of plant, total dry yield,fresh weight of plants and weight of fresh pods, weight of dry roots, chlorophyll SPAD and concentration of N,Pand K% in leaves were estimated. LSD showed superiority of fertilizers application (triple) treatment, (bio+ organic+100% mineral), (bio+organic+50% mineral) for both practice followed by (dual) (0rganic+ 100% mineral) (0rganic+50% mineral),(bio+100%mineral), (bio+50%mineral), (bio+0rganic) and (mono) (100%mineral), (50% mineral),(organic) and (bio) respectively compared with control. (64.25, 54.70, 60.90, 56.80, 54.75, 48.90, 46.70, 50.10, 45.90, 44.10, 41.35and 31.95) cm,( 210.7, 190.5, 172.7,152.3, 144.4,135.6, 136.9, 138.8, 114.0, 123.0, 88.0 and 69.8)gm pot-1 ,(4.05, 3.75, 3.55, 2.85, 2.65, 2.65, 2.35, 3.25.2.95,2.25, 2.35and 2.05) %to the plant height, yield fresh pods and nitrogen concentration in leaves  respectively .